The Need of Attention to Form in Content-Based Instruction - Ruiz-Ayala, Khaterine Gisel (Cinzontle, 2018)
Content subjects refer to subjects where subject matter is learnt via a second language (Van Patten, 2003, p. 28). Schleppegrell, Achugar and Oteiza (2004, p. 68) explain that the basic notion behind these courses is that the learning of an L2 should happen in conjunction with content. Nevertheless, although a new alternative approach to language learning, content based instruction (CBI) represents a challenge to teachers working with content subjects who have been primarily trained to teach a second language. This is due to two main reasons: teachers’ lack of knowledge to teach a second language through content and a lack of knowledge on the subject matter to be taught. This paper focuses on the first issue and reviews the need of attention to form in CBI and the pedagogical practices that could be implemented in these courses in order to pay attention to both form and content in benefit of the learner.